An analysis of medical gel - Vaidya, Sunita N. (Asian Journal of Pharmaceutics (AJP), 2024)
With a focus on sensible topical formulation techniques and the essential components of topical drug delivery systems, the goal of this review is to provide an overview of recent research. The advantage of administering medication topically is that it reaches the site of action directly and remains longer there. Topical medications are primarily administered through the skin, which is one of the body’s most accessible and widely distributed organs. Topical medications are usually very sticky and uncomfortable to apply, which presents a number of challenges. Ointments, lotions, and creams are common topical medications. They also have a lower spreading coefficient, require rubbing, and have a stability problem when compared to other semisolid preparations in the main category. All of these factors have led to an increase in the use of gas in preparations for pharmaceutical and cosmetic uses. The surface tension between a 99% liquid-by-weight colloid and a network of macromolecules composed of minuscule amounts of the surrounding gelatinous substance immobilizes the colloid, forming a gel.